Métodos de superação de dormência de sementes de barbatimão - Martins, Cibele Chalita [UNESP]; Rodriguez da Camara, Armando Tadeo [UNESP]; Machado, Carla Gomes [UNESP]; Nakagawa, Joao [UNESP] (Universidade Estadual de Maringá (UEM), Pro-reitoria Pesquisa Pos-graduacao, 2008)
The aim of this research was to identify methods for breaking dormancy and promoting germination of Stryphnodendron adstringens and S. polyphyllum seeds. Seeds of both species were submitted to the following treatments for breaking dormancy: control; mechanical scarification (sandpaper number 220); hot water (initial temperature of 87 degrees C) for 5 and 15 minutes; chemical scarification with H(2)SO(4) (95%) for 30, 45, 60, 75, 90 and 105 minutes; thermal shock 1 (0 degrees C and 50% RH for 1 h and thereafter 10 minutes into water Ti=85 degrees C, Tf=57 degrees C); thermic shock 2 (40 degrees C and 40% RH for 6 h and thereafter 10 minutes into water, Ti=0 degrees C, Tf=3 degrees C); thermal shock 3 (40 degrees C and 40% RH for 6h and thereafter 10 minutes into water, Ti=25 degrees C, Tf=25 degrees C). We concluded that seeds belonging to same genus but from different species answered differently to some treatments for breaking dormancy. Chemical scarification with H(2)SO(4) (45 minutes) and mechanical scarification with sandpaper are methods that can be employed with efficiency to break dormancy and promote germination for both species.
Methods of breaking dormancy for seeds of Stryphnodendron
Keywords: Stryphnodendron adstringens; Stryphnodendron polyphyllum; Germination; Hard seed